Is the bank credit able to accelerate economic transformation? A multivariate modeling of key sectors in Indonesia - Anam, Yongky Choirul; Lubis, Deltha Airuzsh (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
This study assess how credit provision to MSMEs by sector impacts sectoral economic growth (manufacturing, retail and wholesale trades, transportation, accommodation and food beverage providing, company services, and others services) in 34 provinces in Indonesia, using control variables (population, workforce, and digitalization), as well as dummy variables before and during the COVID-19 pandemic and the economic recovery period. The results of a multivariate regression analysis indicate that credit provision to MSMEs in a sector has a unique effect on other sectors. Interestingly, digitalization has a dominant impact on the Indonesian economy. Priority policies aimed at transforming the national and regional economies can be effectively implemented by providing capital stimulus in the form of business credit to MSMEs, particularly in Indonesia’s leading sectors, and by optimizing the development of ICT facilities and infrastructure.